Survey and New Security methodology of Routing Protocol in AD-Hoc Network - Shahab Wahhab Kareem; Yahya Tareq Hussein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Because of many reasons routing is the complex task in ad hoc sensor network. The self-organizing network which is Mobile ad hoc network (MANET) its established automatically via wireless connections by a combination of portable nodes without the support of a centralized management or static infrastructure. The portable nodes redirect packets among these nodes, enabling connection between nodes outside the range of wireless transmission hop by hop capabilities are necessary. So it important is increasing to provide suitable routing protocol plus security. This paper endeavors to present a full survey about secure routing. At the beginning investigates the reason which makes ad hoc network is susceptible to attacks. After that, it shows the wellknown traditional secure protocols then compares them. Finally, the proposed algorithm depended on the Dynamic Source Routing (DSR) to remove malicious nodes, minimum spanning tree for routing path plus coding-encryption technique of a chaos-based adaptive arithmetic for encrypting, compression plus decompression, decrypt a message.